Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004760.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Creatine for treating muscle disorders

Abstract: Evidence from randomised controlled trials shows that short- and medium-term creatine treatment improves muscle strength in people with muscular dystrophies, and is well-tolerated. Evidence from randomised controlled trials does not show significant improvement in muscle strength in metabolic myopathies. High-dose creatine in glycogenosis type V increased muscle pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 66 publications
1
72
0
7
Order By: Relevance
“…These changes in mtDNA maintenance diseases point to a challenged glutathione supply and suggest that N-acetyl-cysteine supplementation, providing cysteine for glutathione and taurine synthesis, could be tried as a metabolic bypass therapy. Our unbiased screen identified creatine depletion in NMD patients, which was an interesting proof of principle, as a Cochrane review found creatine supplementation to be useful for muscle dystrophies (Kley et al, 2013). However, similarly low global creatine pool, represented by the blood creatine/creatinine ratio, was found to be present in IBM and also in IOSCA, despite the fact that IOSCA patients do not show any muscle phenotype (Lönnqvist et al, 1998) or low muscle mass (Park et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…These changes in mtDNA maintenance diseases point to a challenged glutathione supply and suggest that N-acetyl-cysteine supplementation, providing cysteine for glutathione and taurine synthesis, could be tried as a metabolic bypass therapy. Our unbiased screen identified creatine depletion in NMD patients, which was an interesting proof of principle, as a Cochrane review found creatine supplementation to be useful for muscle dystrophies (Kley et al, 2013). However, similarly low global creatine pool, represented by the blood creatine/creatinine ratio, was found to be present in IBM and also in IOSCA, despite the fact that IOSCA patients do not show any muscle phenotype (Lönnqvist et al, 1998) or low muscle mass (Park et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…It can also enhance muscle strength in certain myopathies, such as muscular dystrophy [3]. Creatine cannot be synthesized in skeletal muscle cells and is transported into skeletal muscle by a Na + -dependent transmembrane protein [4].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic role of creatine supplementation has been largely investigated 72,73 in this regard; there are studies showing that this compound may counteract muscle wasting in animal models, 4 as well as in dystrophic patients. 74,14,75,27 Furthermore, it has been observed that creatine improves glycemic control in diabetic subjects, most likely by enhancing GLUT-4 translocation to the sarcolemma. 76 Studies also suggest that creatine supplementation has a beneficial effect on glucoregulation in skeletal muscle, which may be due to an increase in insulin secretion, activating GLUT-4.…”
Section: Discussionmentioning
confidence: 99%
“…For the measurement CO 2 production, gastrocnemius muscle slices (~100 mg) were incubated in 1.0 ml of Dulbecco buffer (pH 7.4), containing either 5.0 mM of D-glucose + 0.2 mCi D-[U- 14 C] glucose. Before incubation, the reaction medium was gassed with oxygen for 30 s. Flasks were sealed with rubber caps and parafilm.…”
Section: Subjects and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation